1980
DOI: 10.1901/jeab.1980.33-27
|View full text |Cite
|
Sign up to set email alerts
|

Choice and Reinforcement Delay

Abstract: Previous studies of choice between two delayed reinforcers have indicated that the relative immediacy of the reinforcer is a major determinant of the relative frequency of responding. Parallel studies of choice between two interresponse times have found exceptions to this generality. The present study looked at the choice by pigeons between two delays, one of which was always four times longer than the other, but whose absolute durations were varied across conditions. The results indicated that choice is not u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0
1

Year Published

1988
1988
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 20 publications
(47 reference statements)
4
42
0
1
Order By: Relevance
“…This "failure" may not be a problem with procedures using equal-duration terminal links (see Gentry & Marr, 1980;Poniewaz, 1984; and the introduction to Experiment 2). The suggestion that, in the conventional procedure, the necessarily shorter duration of the higher reinforcer rate terminal-link schedule (hence, the more immediate production of reinforcers on subsequent trials) could add to the reinforcing value of that outcome (Mazur et al, 1985;Shull & Spear, 1987) is supported by the apparently clear different asymptotic levels of choice in the constant terminal-link duration procedure (Gentry & Marr, 1980; and the present experiment) compared with the procedure in which terminal-link delays and durations are perfectly correlated (Davison & Temple, 1973;Duncan & Fantino, 1970;Williams & Fantino, 1978). The real possibility is that, with the added reinforcement of returning to the initial link equalized between the choices, modeling concurrent-chain performance will be simplified considerably.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This "failure" may not be a problem with procedures using equal-duration terminal links (see Gentry & Marr, 1980;Poniewaz, 1984; and the introduction to Experiment 2). The suggestion that, in the conventional procedure, the necessarily shorter duration of the higher reinforcer rate terminal-link schedule (hence, the more immediate production of reinforcers on subsequent trials) could add to the reinforcing value of that outcome (Mazur et al, 1985;Shull & Spear, 1987) is supported by the apparently clear different asymptotic levels of choice in the constant terminal-link duration procedure (Gentry & Marr, 1980; and the present experiment) compared with the procedure in which terminal-link delays and durations are perfectly correlated (Davison & Temple, 1973;Duncan & Fantino, 1970;Williams & Fantino, 1978). The real possibility is that, with the added reinforcement of returning to the initial link equalized between the choices, modeling concurrent-chain performance will be simplified considerably.…”
Section: Resultsmentioning
confidence: 99%
“…This discussion therefore suggests that the hyperbolic model is a serious contender for describing concurrent-chain procedures that use equal terminal-link durations. Under these conditions, the model does predict an increase in preference as the terminal-link delays are increased, and the available data (Gentry & Marr, 1980) The subjects and apparatus were the same as in Experiment 1. The procedure was the same as described in the General Procedure; the sequence of experimental conditions is shown in Table 3.…”
Section: General Methods Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…He found that preferences for the single-reinforcer terminal link were reduced when he added time after the single reinforcer (post-reinforcer delay, or PrD) so that the overall duration of the single-reinforcer terminal link equaled that of the multiple-reinforcer terminal link. this procedure was not new, since it had previously been used in Gentry and Marr (1980), Poniewaz (1984), and Snyderman (1983). Mazur found that in certain circumstances, preference for the single-reinforcer terminal link would be above 50% with no PrD, but below 50% when a PrD was added.…”
Section: Apparatusmentioning
confidence: 99%